A Proposal for a Rat Model of Spinal Cord Injury Featuring the Rubrospinal Tract and its Contributions to Locomotion and Skilled Hand Movement - Morris, Renée; Whishaw, Ian Q. (Frontiers in Neuroscience, 2016)
Spinal cord injury and repair is a dynamic field of research. The development of reliable animal models of traumatic spinal cord injury has been invaluable in providing a wealth of information regarding the pathological consequences and recovery potential of this condition. A number of injury models have been instrumental in the elaboration and the validation of therapeutic interventions aimed at reversing this once thought permanent condition. In general, the study of spinal cord injury and repair is made difficult by both its anatomical complexity and the complexity of the behavior it mediates. In this perspective paper, we suggest a new model for spinal cord investigation that simplifies problems related to both the functional and anatomical complexity of the spinal cord. We begin by reviewing and contrasting some of the most common animal models used for investigating spinal cord dysfunction. We then consider two widely used models of spinal deficit-recovery, one involving the corticospinal tracts (CTS) and the other the rubrospinal tract (RST). We argue that the simplicity of the function of the RST makes it a useful model for studying the cord and its functional repair. We also reflect on two obstacles that have hindered progress in the pre-clinical field, delaying translation to the clinical setup. The first is recovery of function without reconnection of the transected descending fibers and the second is the use of behavioral paradigms that are not under the control of the descending fiber pathway under scrutiny.